2019
DOI: 10.1021/acscombsci.8b00129
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Catalytic Nucleic Acids on Porphyrin Metalation and Peroxidase Activity by in Vitro Selection of Aptamers for N-Methyl Mesoporphyrin IX

Abstract: To develop a novel light-up probe and DNAzyme, we selected aptamers for N-methyl mesoporphyrin IX (NMM), a common fluorogenic analogue of coenzyme hemin, by a modified affinity chromatography-based systematic evolution of ligands by exponential enrichment (SELEX). Two truncated aptamers Nm1 and Nm2 with low micromolar dissociation constants (0.75 and 13.27 μM) were obtained after 11 rounds of selection and the final minimized 39-mer aptamer Nm2.1 showed 24-fold fluorescence enhancement for NMM at saturated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
(67 reference statements)
0
15
0
Order By: Relevance
“…Thus, the ability of NMM aptamers to accelerate metal insertion (chelatase activity) seems to be positively correlated with their binding affinity for NMM. Nm2 also displayed peroxidase activity in the presence of hemin [13]. Recently, Li et al developed a gold nanoparticle-based SELEX method and identified an aptamer for NMM and ZnPPIX.…”
Section: Discovery Of Nmm As a Gq Ligand And The Development Of Nmm Amentioning
confidence: 99%
“…Thus, the ability of NMM aptamers to accelerate metal insertion (chelatase activity) seems to be positively correlated with their binding affinity for NMM. Nm2 also displayed peroxidase activity in the presence of hemin [13]. Recently, Li et al developed a gold nanoparticle-based SELEX method and identified an aptamer for NMM and ZnPPIX.…”
Section: Discovery Of Nmm As a Gq Ligand And The Development Of Nmm Amentioning
confidence: 99%
“…After establishment of a DNA oligonucleotide chain library, it is necessary to screen for and enrich oligonucleotide chains that can bind to target molecules with high specificity and affinity. Mature screening techniques include magnetic bead separation[20], high-speed centrifugation, affinity chromatography[21], capillary electrophoresis[22], and nitrocellulose membrane filtration[23]. For example, studies have shown that a target aptamer can be obtained in only four cycles of capillary electrophoresis SELEX[24].…”
Section: Selex Methods For Screening Aptamersmentioning
confidence: 99%
“…Recently, efforts have been made to select non-G4 metalation DNAzymes (Yang et al, 2019), and the effect of metal ions has been examined in more detail. A recent effort obtained a DNA aptamer with a high binding affinity toward MPIX but without a predictable G4 structure.…”
Section: G-quadruplex Containing Dnazymesmentioning
confidence: 99%